Waldmeier Effect in Stellar Cycles - Garg S.; Karak B.B.; Egeland R.; Soon W.; Baliunas S. (My University, 2025)
One of the most robust features of the solar magnetic cycle is that the stronger cycles rise faster than the weaker ones. This is popularly known as the Waldmeier Effect, which has been known for more than 100 yr. This fundamental feature of the solar cycle has not only practical implications, e.g., in predicting the solar cycle, but also implications in understanding the solar dynamo. Here we ask whether the Waldmeier Effect exists in other Sun-like stars. To answer this question, we analyze the Ca ii H and K S-index from Mount Wilson Observatory for 21 Sun-like G-K stars. We specifically check two aspects of Waldmeier Effect, namely, (1) WE1: the anticorrelation between the rise times and the peaks and (2) WE2: the positive correlation between rise rates and amplitudes. We show that, except for HD 16160, HD 81809, HD 155886, and HD 161239, all stars considered in the analysis show WE2, while WE1 is found to be present only in some of the stars studied. Furthermore, the WE1 correlation is weaker than the WE2. Both WE1 and WE2 exist in the solar S-index as well. Similar to the solar cycles, the magnetic cycles of many stars are asymmetric about their maxima. The existence of the Waldmeier Effect and asymmetric cycles in Sun-like stars suggests that the dynamo mechanism which operates in the Sun is also operating in other stars. © 2019. The American Astronomical Society. All rights reserved.